ChemInform Abstract: Contrasting Reactivity of CS2 with Cyclic vs. Acyclic Amidines. Issue 14 (March 2016) - Ang, M. Trisha C.; Phan, Lam; Alshamrani, Aliyah K.; Harjani, Jitendra R.; Wang, Ruiyao; Schatte, Gabriele; Mosey, Nicholas J.; Jessop, Philip G.
Abstract: The title reactions are investigated in detail.